Kerja Sama G20 dalam Pemulihan Ekonomi Global dari COVID-19 - Wiwiek Rukmi Dwi Astuti (Andalas Journal of International Studies (AJIS), 2020)
This study reveals the institutional performance of the G20 in order to help global economy recovery because of COVID-19. This study uses qualitative methods, providing in-depth descriptions through internet-based research as data-based techniques. This study indicates that G20 has proven its performance in carrying out a multilateral cooperation system through collective responses, which contain six dimensions, namely yaitu domestic political management; deliberation; direction setting; decision making; and development of global governance. G20's coordination creates a global network that includes interactions between international institutions, namely the IMF, WTO, and World Bank, as well as regional organizations and informal partnerships in the arena of international cooperation.